Urinary Congophilia Confirmed With the CapCord Test Is Associated With Pregnancy Outcomes in Women With Early-Onset Pre-eclampsia - Cai, Benshuo; Yuan, Xiaoying; Li, Xingmin; Xu, Jun; Du, Juan (Frontiers in Medicine, 2021)
Background: The association between misfolded proteins presented in the urine of pregnant women and pregnancy outcomes associated with early-onset pre-eclampsia (PE) remains unclear. This study aimed to investigate this association to examine the predictive value of urinary congophilia in the prognostication of pregnancy outcomes in this patient group in the Chinese population. Materials and Methods: This study included 1397 patients, of which 46, 147, and 8 patients had gestational hypertension, PE, and chronic hypertension, respectively, and 1196 were healthy controls undergoing the CapCord test for urinary congophilia. Patients with PE were divided into early- and late-onset groups. Patients with early-onset PE were further divided into iatrogenic prematurity and full-term delivery groups, the rates of urinary congophilia were compared between the groups; additionally, this patient group was divided into positive and negative urinary congophilia groups, clinical characteristics and pregnancy outcomes were compared between the groups. Univariate and multivariate logistic regression analyses were performed. Results: A total of 113 (76.9%) of 147 patients in the PE group had urinary congophilia; this rate was higher than that observed in the other three groups (2=780.892, p<0.001). Gestational age in the early-onset PE group at both onset and delivery was lower than that in the late-onset PE group (p<0.001). The rates of iatrogenic prematurity and hemolysis, elevated liver enzymes, and low platelet count syndrome were both higher in the early-onset PE group than in the late-onset PE group (p<0.001, p<0.05). In addition, the rate of urinary congophilia in the early-onset PE group was higher than that in the late-onset PE group (2=13.297, p<0.001). Urinary congophilia was an independent risk factor for iatrogenic prematurity among patients with early-onset PE in both univariate (odds ratio [OR] 17.143, 95% confidence interval [CI]: 4.719–62.271; p<0.001) and multivariate (OR 18.174; 95% CI: 4.460–74.063; p<0.001) analyses. Patients with early-onset PE and urinary congophilia were more likely than their counterparts without urinary congophilia to deliver at a lower gestational age, present with iatrogenic prematurity, and have a shorter latency period between onset and delivery. Conclusion: Urinary congophilia confirmed with the CapCord test may help predict pregnancy outcomes in patients with early-onset PE.